Coenological and synphysiological investigation on loess grassland vegetation (Salvio-Festucetum rupicolae) close to Gödölló Hills (Hungary) - Tibor Szerdahelyi; Szilvia Foti; Szilard Czobelj; Janos Balogh; Zoltan Nagy; Zoltan Tuba (Acta Biologica Slovenica, 2004)
Parallel coenological and synphysiological examinations were carried out on three typical xerophilous loess grassland stands of Salvio-Festucetum rupicolae community in the Gödöllö Hills, near Isaszeg village. Three stand types, a Carex humilis, a Chamaecytisus austriacus and a Stipa dasiphylla dominated ones were investigated at the same spatial scale (mesoscale). In our sample area apparent dominance by three species (Festuca rupicola, Stipa dasiphylla, and Carex humilis) suggested that these stands of this subassociation have been emerged from three types of differing species composition. According to these analyses three groups dominated by Carex humilis, Chamaecytisus austriacus and Stipa dasiphylla of festucetosum rupicolae subassociation of a stand of Salvio-Festucetum rupicolae association were separated. Results of the synphysiological measurements show, that water shortage and senescence in autumn are responsible for the different physiological performances of the three types. In the well-watered summer period we found significant difference only between the physiological activity of the Carex- and Chamaecytisus- dominated types, however this difference is due to the significant LAI-difference and after relating photosynthesis to 1 m2 leaf area, the difference is non-significant.